Risk behaviors for STIs and HIV in the Commonwealth of the Northern Mariana Islands - DeLisle, Brenda (Curtin University, 2012)
Background: At the end of 2009, there were 33.3 million people living globally with the Human Immunodeficiency Virus (HIV) with 2.6 million new infections occurring annually (UNAIDS, 2010). In the Commonwealth of the Northern Mariana Islands (CNMI) in the Western Pacific Ocean, annual STI and HIV statistics as of 2009, indicate that syphilis, hepatitis B and herpes simplex virus are at their highest rates since 2002. This study documented the understanding of the social, risk and sexual behavior among a cross-section of the population in the CNMI. The primary objective of the study was to establish baseline behavioral data on STIs and HIV/AIDS in the CNMI.Methods: Behavioral information was obtained using a modified version of a survey based on the Family Health International STI/HIV/AIDS Behavioral Survey for adults adapted specifically for use in the CNMI. The questionnaire was administered to three population groups in the CNMI: The first consisted of pregnant women (n=228) who were attending their first prenatal visit and who had not been previously tested for STIs. The second consisted of men (n= 132) over 18 years of age who had engaged in sex with another man during the last five years. The third group consisted of male and female youth (n=433), aged between 18-24 years, were unmarried or had been living with a partner for less than 12 months prior to the survey date. The survey comprised of a variety of questions including personal background history, marital history, sexual partner history, sexually transmitted infection history, condom usage, alcohol and drug use. Additional information was obtained on the participant’s level of HIV/AIDS knowledge and access to HIV testing.Analysis: The data was analyzed using SPSS Statistics Version 17. Frequencies of all the variables were undertaken and bivariate analysis was conducted to determine statistical association between continuous and categorical data. Chi-Square analysis was used to determine if differences existed between prevalence figures and categorical variables and analysis of variance (ANOVA), was used to determine if differences existed between continuous variables.Key Findings: Results from the prenatal survey group indicated that the majority of the respondents (66%) were unmarried, unemployed Micronesians (54%) who had never used a condom and who were not using any form of birth control. Most were living with a partner (70%), and none had ever injected drugs. Information about STIs and HIV was obtained through the television, newspaper, the internet, radio and friends. The majority of pregnant women (94%) were aware that they could pass HIV on to their unborn child, however a quarter of the women were not aware that they could pass HIV through breastfeeding. During the last twelve months, the majority of women (99%) had only one sex partner, a large percentage had never used a condom, and the most common self-reported STI diagnosis was chlamydia.Data results from the MSM survey group indicated the majority of participants (60%) were Micronesian, well-educated with 91% having completed university or college or graduated high school yet unemployment and not living with a regular partner. Most MSM had multiple oral and anal sex partners. A third of those who travelled overseas in the last 12 months (27%) had sex while away; the majority of those were male partners, most did not use a condom and the most common self-reported STI diagnosis was HIV (11%).Data results from the youth survey group indicated that the majority of participants were born in CNMI and currently reside with family. The majority of participants had had sex and a significantly higher proportion of males had had sex than females. Approximately half of the participants had sex without a condom in past 12 months. More females than males had been diagnosed with an STI in the past 12 months chlamydia was the most common STI reported. Youth participants had the highest rates of substance and drug use for betel nut and marijuana and the second highest overall use for tobacco. The majority of youth reported having used drugs (amphetamines, ecstasy, inhalants, hallucinogens and cocaine). The results also revealed that youth were least likely of the three groups to have accurate knowledge on HIV. HIV testing was low across in the youth group. The media has played a large role in educating participants with most participants reporting having heard messages about HIV on TV, then the radio, newspapers and billboards. A large number of youth sought HIV knowledge through the internet.Conclusion: This study presents data on several aspects of risk behavior in the CNMI and documents several risk behaviors (sexual, drug usage and STI history) that provide a starting point for improving preventive healthcare and health promotion programs and increasing healthcare funding in the CNMI. Findings include low HIV testing rates, low HIV knowledge, significant internet usage for HIV/STI information, low off-island travel rates and low rates of condom use. The recommendations proposed can be incorporated into the STI and HIV management programs. This study acknowledges the importance of HIV testing and interventions to improve ST and HIV testing in the CNMI need to be considered. Finally, a recommendation is also made to build on this study to enable further research and testing in the CNMI.